“Hopeless but supported in that hopelessness”: a qualitative study of how people experience talking to a GP about suicide - Fedorowicz, Sophia; Dempsey, Robert C.; Ellis, Naomi; Gidlow, Christopher (Frontiers in Psychiatry, 2026)
IntroductionThere is evidence that help-seeking escalates in the weeks before death by suicide, with general practice being the most common last point of contact. The experiences of people seeking support for suicidal thoughts and feelings in primary care is under-explored. Understanding the perspectives of people experiencing suicidal thoughts and feelings may identify innovative ways to assess risk in primary care in a safe and collaborative way, allowing more opportunity for intervention. The aim of the current qualitative study was to explore individual experiences of talking to a GP about suicide to understand how they perceive these interactions.MethodsThis study was developed with people who have lived experience of suicidality and support seeking, who also supported the interpretation of data and informed the dissemination plan. A participatory, consultative approach was adopted, with experts by experience involved flexibly at multiple stages of the research. Participation was strengths-based and care-informed, prioritising choice, comfort, and psychological safety. Data were collected using an online qualitative survey that was distributed using social media. Forty-one responses were inductively analysed using Reflexive Thematic Analysis. Participants were aged between 19 and 67 years old, 29 were female, nine male, two non-binary, and one did not disclose their gender.ResultsThree overarching themes were identified: 1) Challenges disclosing suicidal thoughts and feelings: “I wish she would just say suicide”; 2) GP limitations: “I felt my medical needs were met, but not necessarily my mental health needs”; 3) Creating a safe space: “He made it normal, not embarrassing or weird.” This study identified a range of factors influencing how people experience talking to a GP about suicide, including stigma, fear of the consequences of disclosing suicidality, the resources available to GPs generally (e.g., training and knowledge of suicide prevention), and GPs’ active listening skills.DiscussionThese findings have implications for practice largely connected to a need for relationally informed responses to suicidality that promote more compassionate, contextually responsive mental health care. Methodologically, the paper demonstrates the value of participatory, lived experience–led research grounded in trust, reciprocity, and collaboration beyond tokenism.